Study on effects of the hydroxyl group position and carbon chain length on combustion and emission characteristics of Reactivity Controlled Compression Ignition (RCCI) engine fueled with low-carbon straight chain alcohols. (15th January 2022) - Zhong, Yingzi; Han, Weiqiang; Jin, Chao; Tian, Xiaocong; Liu, Haifeng
Abstract: Effects of hydroxyl group position (OHP) and carbon chain length (CCL) on combustion and emission characteristics of Reactivity Controlled Compression Ignition (RCCI) engine under different oxygen mass contents (Ro ) and start of injections (SOI) were experimentally studied, and real influence factors and sequence of OHP, CCL, Ro and SOI were analyzed quantitatively. Results indicated that: ①Factors having effects on characteristics were not necessarily real influence factors. For example, HC decreased with SOI advance, while they were not correlated. ②Real influence factors and sequence of CA10, CA50 and CA90 were only SOI, ignition delay (ID) was SOI > Ro, indicated mean effective pressure (IMEP) and indicated thermal efficiency (ITE) were CCL > Ro > OHP, HC was Ro > CCL > OHP, CO was CCL > Ro, NOx and particle mass concentration (PMC) were only SOI, while particle number concentration (PNC) and particle average diameter (PAD) were Ro > CCL > SOI. ③OHP and CCL were real influence factors for partial characteristics. IMEP, ITE and HC were correlated to OHP and CCL, and more sensitive to CCL, while CO, PNC and PAD were only correlated to CCL. ④Consumption pathway change aroused by OHP or CCL change was probably primary cause for HC, CO, PNC and PAD change without combustion phase change. Highlights: Effects of hydroxyl group position and carbon chain length are studied. Real influence factors and their sequence for different characteristics are analyzed. Factors having effect on a characteristic are not necessarily real influence factors. Carbon chain length is related to more characteristics than hydroxyl group position. Sensitivity to carbon chain length is much stronger than hydroxyl group position.